The Effect of Paternalistic Leadership on Organisational Ethical Climate: The Role of Organisational Justice As A Moderating Variable - Anindya Diah Mentari; Claudius Budi Santoso (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
This study examines the effect of paternalistic leadership on organisational ethical climate and the role of organisational justice as a moderating variable. The relationship of paternalistic leadership and ethical climate is explained through social learning theory. The respondents used in this study are employees of public organisations as an alternative to the for-profit organisations that previous empirical studies have tended to use. The testing of this model uses the hierarchical regression analysis. The findings of this study confirm the results of earlier studies that paternalistic leadership has a positive and significant impact on organisational ethical climate, particularly in public organisations. The results also show that organisational justice has a moderating role in strengthening the positive influence of paternalistic leadership on organisational ethical climate. The contribution of this study is that, based on contextual factors, effective paternalistic leadership influences the ethical climate in public organisations. Keywords: organisational ethical climate, organisational justice, paternalistic leadership, public organisations